2013
DOI: 10.1371/journal.pone.0067791
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Increase in N-3/N-6 Fatty Acid Ratio Reduces Maternal Obesity-Associated Inflammation and Limits Adverse Developmental Programming in Mice

Abstract: Maternal and pediatric obesity has risen dramatically over recent years, and is a known predictor of adverse long-term metabolic outcomes in offspring. However, which particular aspects of obese pregnancy promote such outcomes is less clear. While maternal obesity increases both maternal and placental inflammation, it is still unknown whether this is a dominant mechanism in fetal metabolic programming. In this study, we utilized the Fat-1 transgenic mouse to test whether increasing the maternal n-3/n-6 tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
94
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 82 publications
11
94
1
1
Order By: Relevance
“…Our laboratory has used a Fat1 transgenic mouse model (which can endogenously convert ω6 fatty acids to ω3 fatty acids) to test the effect of increasing the maternal ω3 to ω6 tissue fatty acid ratio during highfat diet consumption. Wildtype offspring of Fat1 dams had decreased hepatic lipid accumulation and were protected from highfatdietinduced inflammation 27 . Thus, increasing the maternal ω3 to ω6 fatty acid ratio and reducing placental inflammation might be a promising target for improving outcomes in the fetus of a mother with obesity consuming a highfat diet.…”
Section: Targeting the Gut–liver Axismentioning
confidence: 99%
“…Our laboratory has used a Fat1 transgenic mouse model (which can endogenously convert ω6 fatty acids to ω3 fatty acids) to test the effect of increasing the maternal ω3 to ω6 tissue fatty acid ratio during highfat diet consumption. Wildtype offspring of Fat1 dams had decreased hepatic lipid accumulation and were protected from highfatdietinduced inflammation 27 . Thus, increasing the maternal ω3 to ω6 fatty acid ratio and reducing placental inflammation might be a promising target for improving outcomes in the fetus of a mother with obesity consuming a highfat diet.…”
Section: Targeting the Gut–liver Axismentioning
confidence: 99%
“…In that study, wild-type mice fed with a high-fat diet exhibited a high serum concentration of 12 pro-inflammatory cytokines (p<0.05), but no such increase was observed in the transgenic mice [23]. Depner et al reported that among n-3 LC-PUFAs, DHA was more effective than…”
Section: Discussionmentioning
confidence: 83%
“…The release of GGT typically increases oxidative stress [39]; however, serum GGT levels were relatively decreased in this study, indicating that oxidative stress was reduced. Furthermore, GGT has been strongly associated with body lipids, particularly visceral fat, which contribute to the progression of NAFLD [23,24,40].…”
Section: Weta Et Almentioning
confidence: 99%
“…Kasbi-Chadli et al have recently reported that n-3 PUFA maternal supplementation, which caused the n-6/n-3 PUFA ratio in the maternal diet to decrease from 49.4 to 3.0, reduced the n-6/n-3 PUFA ratio in the plasma of dams and alleviated the metabolic disorders in the adult offspring with diet-induced obesity [44]. Heerwagen et al demonstrated that transgenic mice that decrease in the n-6/n-3 tissue PUFA ratio from 20-50 to 1 reduced maternal obesity-associated inflammation and prevented metabolic impairments in adult offspring [45]. The n-6/n-3 PUFA ratio in these three studies was much more modulated than that in our study, and these three studies basically examined the effects of the n-6/n-3 PUFA ratio on obesity-related disorders in mother and offspring.…”
Section: Discussionmentioning
confidence: 99%